ANALISA AERODINAMIKA BODY MOBIL HEMAT BAHAN BAKAR ANTAWIRYA KONSEP 3 DENGAN MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS - Rizkya Laila Nursyahbani; MSK. Tony Suryo Utomo (JURNAL TEKNIK MESIN, 2015)
Fuel oil declining from year to year since oil resources of the earth are not renewable. Hence, a fuel saving plan is something of considerable importance today. Continued development of technology has enabled automotive engineers to place an emphasis on vehicle fuel consumption by keeping the drag coefficient (Cd) value to minimum, which in turn should improve fuel efficiency. This research is aimed at effort to prouce a more aerodynamic car body design, particularly to redesign the previous Antawirya car known as Antawirya Konsep 3, to simulate and compare the results of both cars, in term of the drag coefficient values, and to learn about the air flow pattern around the car. Car aerodynamics simulation are conducted in wind tunnel set as the computing domain by Computational Fluid Dynamics (CFD). The k-epsilon turbulent realizable standard wall function method is used in this research, which is specified based on the phenomenon of validation in backward-facing step. This research also use the second order upwind as the discretization method for more accurate results. The number of each grid for previous Antawirya and Antawirya konsep 3 are 862391 and 639641. The results of the simulation show a reduction of drag coefficient on Antawirya konsep 3 compare to the previous Antawirya. Drag coefficient has shown a decrease by 24,93% at a rate of 10 km/h, a decrease by 25,20% at 20 km/h, a decrease by 26,01% at 30 km/h, a decrease by 26,02% at 40 km/h, a decrease by 26,37% at 50 km/h, and a decrease by 25,83% at 60 km/h. The separation and wake phenomenon also occurred on the back of the car body, as the separation and wake on Antawirya konsep 3 are shorter than the previous Antawirya design. This is due to the fact that the body of Antawirya konsep 3 has a more aerodynamic.